Limited strength of short fiber composites: Identification of variables affecting the critical fiber length - Shiino, Marcos Yutaka [UNESP]; Monticeli, Francisco Maciel [UNESP]; Donadon, Maurício Vicente (SAGE Publications, 2023)
The industry of composite materials has grown in the last decade due to the requirements of light and high strength materials. The increasing demands of materials have to comply with low greenhouse gases emissions (GHG) as stated by international agreements, and reusing and recycling is a path to minimize the environmental impacts. This research aims to analyze the variables that influence the tensile strength of discontinuous laminate composites of short fibers from cutting operation process which is in the context of reusing. These variables were part of the equation of force equilibrium that involves shear strength failure criterium approach. In addition, the failure analysis and the results were compared with the literature data. Composites of glass fiber fabric wastes with varied fiber length (defined as short fiber) was designed and tested using polyethylene terephthalate (PET) as a matrix. A total of three different laminates with different fabric lengths were evaluated, totaling of seven interruptions/discontinuities along the thickness of each laminate. An image analysis of the failure sequence aided to assess the laminate behavior by comparing the stress–strain curve shape and they were in agreement with the results provided by the developed equation. The results show that this equation enables to identify the variables that influence the laminate strength: yielding stress; interface strength; stress concentration; and peel stress. In this particular research, the weak interface contributed to the low tensile strength of the laminates, and showed less influence of the “critical length,” limiting the micromechanical approach that considered a fiber filament.
Keywords: adhesive failure; Compression molding; critical fiber length; load transfer; Tresca’s criterion